A formação em nutrição no estado de Sergipe - Lessa, Marília Prudente Freire (2024)
The nutritionist is a professional qualified to work in all processes associated with food and nutrition, with the aim of promoting health, ensuring food safety and preventing diseases, both individually and collectively, and at all stages or cycles of life. The National Curricular Guidelines for the Nutrition course states that courses should train professionals with a generalist profile, able to work to promote, maintain and recover of the nutritional status of individuals or population groups, based on ethical principles, and with skills to reflect on the context social, political, economic and cultural of society, with an emphasis on the Unified Health System (Sistema Único de Saúde – SUS). The current epidemiological-nutritional profile of the population associated with the different realities of individuals, reiterates the need to reflect on the training model for nutritionists. Therefore, this study aimed to analyze training in Nutrition in Higher Education Institutions in the state of Sergipe. This research resulted in three manuscripts, in which data was collected remotely, via Google Forms, supported by the study by Magalhães et al. (2022), which confirms how promising and effective remote research has become. Both questionnaires (for professors and for students) were made up of open and objective questions. As for 1 st manuscript, a descriptive cross-sectional study was carried out, of a qualitative and quantitative nature, with internship coordinators, professors and internship preceptors of all Nutrition courses in the state of Sergipe. It found that Nutrition training in the state is reductionist and limited aspects on the public health area. The scenario presented by the participants proved to be challenging, both in relation to the difficulties of teaching itself, and local and national public policies. These challenges have an impact on the teaching-learning process and, mainly, on for professional practice. Regarding 2nd manuscript, a cross-sectional analytical study, of a quantitative nature was carried out. The research universe comprised graduates of the undergraduate course in Nutrition at the Federal University of Sergipe. It emerged that satisfaction with their training and dissatisfaction with professional practice was mainly due to low wages. Furthermore, dissatisfaction is linked to working in a field that is not their preferred one. As for the 3 rd manuscript, a longitudinal, observational and analytical study was carried out with graduates of the Nutrition course at the Federal University of Sergipe. The evaluation showed that although the positive perception of the course has increased over the years, professional satisfaction has not followed suit, revealing weaknesses such as working conditions, which include adequate workload without overload, adequate wages and professional valorization. Finally, it is of fundamental importance to continue researching with the professor staff and students, as it prompts reflections and provides points for reinventing for individuals